Influence of residual stress on stress concentration factor for high strength steel welded joints - Jiang, Jin (2013)
In this study, a set of plate-to-plate T and Y joints specimens made from high strength steel plates with yield stress equal to 690 MPa is investigated. The joints are fabricated by SMAW welding procedure. Two groups of specimens with different welding procedures are included: one group is composed by the joints with welding completed at ambient temperature and the other group is composed by the joints with welding completed at a preheating temperature of 100 °C. The residual stress near the weld toe is investigated for both groups. Hole-drilling method is applied to investigate the residual stress distribution and variation in joints. Sequentially coupled thermal-stress analysis is then conducted with finite element package ABAQUS to investigate the residual stress distribution in the joints. Finally, the effects of residual stress on the stress concentration factor distributions of the joints are evaluated. A new parameter is put forward in stress concentration factor evaluation to combine the residual stress effect.